Phylogenetics of Morus (Moraceae) inferred from ITS and trnL-trnF sequence data - Nepal, Madhav P.; Ferguson, Carolyn J. (My University, 2012)
Morus (Tribe Moreae, Moraceae) consists of ca. 13 species of trees distributed in Asia, Africa, Europe, and North, Central, and South America. The broad geographical distribution of the genus, overlapping ranges of many taxa, and documented hybridization between some species present interesting questions of taxonomy, phylogeny, and biogeography. Phylogenetic data for Morus also contribute to higher level taxonomic work in the family. We used sequence data from ITS of the nrDNA and the chloroplast trnL-trnF intergenic spacer to study phylogenetic relationships of Morus. Phylogenies based on separate data sets were not statistically incongruent, and the combined tree reveals that Morus, as currently circumscribed, is non-monophyletic. Subgenus Morus (sensu Leroy) is resolved as a clade and consists of two well-supported clades: one of Asian taxa and one of North American taxa. Sampled members of the genus Trophis (two, including the type) form a clade sister to subgenus Morus. Morus mesozygia (Africa; subgenus Afromorus) and M. insignis (Neotropics; subgenus Gomphomorus), which have not been included to date in other phylogenetic studies of the family, are placed outside the subgenus Morus-Trophis clade. This work is an important step in elucidating relationships of Morus and along with other recent phylogenetic studies in Moraceae, underscores the need for further work within Tribe Moreae to clarify natural generic relationships.
Keywords: ITS; Moraceae; Moreae; Morus; Phylogeny; trnL-trnF